Computer-Aided Detection, Modelling And Diagnostic Techniques For Biliary Structure Using MRCP - Logeswaran., R. (2006)
Magnetic Resonance Cholangiopancreatography (MRCP) is a special sequence of MRI (Magnetic Resonance Imaging) focusing on the pancreato-biliary system. The objective of this research is to develop semi-automated analysis and diagnosis techniques useful for detection, modelling and preliminary diagnosis of some diseases affecting the biliary ducts, using 2D MRCP images.